Video consultations in ordinary and extraordinary times. Issue 5 (29th August 2020) - Duncan, Callum; Macleod, Angus D
Abstract : Tele-neurology is a neurological consultation at a distance, or not in person, using various technologies to achieve connectivity, including the telephone and the internet. The telephone is ubiquitous and is a standard part of how we manage patients. Video consulting has been used for a long time in some centres, particularly in those where the geography means that patients have to travel long distances. Various technologies can be used, and with the development of various internet-based video-calling platforms, real-time video consulting has become much more accessible. We have provided a tele-neurology service in the North East of Scotland since 2006 using video conferencing with far-end camera control. More recently, we have complemented this using an internet-based platform (NHS Near Me). Here we outline the practicalities of video consulting in 'ordinary' times and comment on its use in the 'extraordinary' times of the coronavirus pandemic.